Instytucja dobrowolnego poddania się odpowiedzialności w prawie karnym skarbowym i jej wpływ na postępowanie sądowo-administracyjne - Frąckowiak, Kamil (Kwartalnik Prawa Publicznego, 2013)
Voluntary submission to liability is one of the basic institutions of punishment decrease in fiscal penal law. The perpetrator of a fiscal offence derives considerable benefits in fiscal penal proceedings: the judgment in which the court permits the perpetrator to voluntarily accept liability is not entered in the National Criminal Register, and at the same time it does not constitute grounds for finding the person a repeated fiscal offender. On the other hand the institution conducting the proceeding recovers public-law debt. Despite the undeniable benefits arising from voluntary submission to liability – in matters of criminal tax cases – its indiscriminate use may cancel the chances of the suspected perpetrator in the overall evaluation of evidence in the administrative judicial proceedings. At the junction of these proceedings the problem appeared in the interpretation of the judgments based on the voluntary submission to liability of the offender – the administrative courts consider them as convictions. The result is that the administrative courts and tax authorities are bound by article 11 of administrative judicial proceedings Act. The author upheld the view that the institution of voluntary submission to liability is not the judgment of conviction and it cannot be interpreted broadly.